2020
DOI: 10.3389/fcell.2020.585987
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Therapeutic Approach for Colorectal Cancer Stem Cells: Blocking the PI3K/Akt Signaling Axis With Caffeic Acid

Abstract: Cancer stem cells (CSCs) have been identified in a multiple of cancer types and resistant to traditional cancer therapies such as chemotherapeutic agents and radiotherapy, which may destroy bulk tumor cells but not all CSCs, contributing to reformation tumor masses and subsequent relapse. Moreover, it is very difficult to effectively identify and eliminate CSCs because they share some common phenotypic and functional characteristics of normal stem cells. Therefore, finding better therapeutic strategies to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 61 publications
1
12
0
1
Order By: Relevance
“…Furthermore, it also inhibited the PI3K/AKT signal pathways, making it the first reported CDK4/6 plus PI3K/AKT muti-kinase inhibitor. Recent data indicated that the PI3K-AKT-mTOR signaling pathway plays an important role in the self-renewal of cancer stem cells and resistance to chemotherapy or radiation therapy (Park et al, 2020;Hou et al, 2021). Therefore, aminoquinol may be more effective for HCC and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it also inhibited the PI3K/AKT signal pathways, making it the first reported CDK4/6 plus PI3K/AKT muti-kinase inhibitor. Recent data indicated that the PI3K-AKT-mTOR signaling pathway plays an important role in the self-renewal of cancer stem cells and resistance to chemotherapy or radiation therapy (Park et al, 2020;Hou et al, 2021). Therefore, aminoquinol may be more effective for HCC and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Another report concluded that RA mediated the inhibition of melanoma cell proliferation, migration and invasion and promoted apoptosis by ameliorating ADAM17/EGFR/AKT/GSK3β axis (Huang et al 2021 ). The above findings reveal that PI3K-Akt signaling is a crucial biological target for RA in cancer cells (Lee et al 2018a , 2018b ; Ko et al 2019 ; Park et al 2020 ; Kim et al 2020b , 2021a ). On the contrary, in another study, RA acted as a radioprotector in healthy cells but caused significant damage to melanoma cells in irradiated cultures.…”
Section: Clinical Implications Of Ramentioning
confidence: 91%
“…GA downregulates protein levels of p-AKT, PI3K, and mTOR affecting cell viability, proliferation, invasion, and angiogenesis in lung cancer, ovarian cancer, and glioma cells [ 48 , 131 , 132 ]. p-Akt was significantly decreased by CA on colorectal cancer stem cells [ 133 ]. In prostate cancer cells, breast cancer cells, and pancreatic cells, Qu binds PI3K suppressing AKT phosphorylation and inducing apoptosis by regulation of the Bax, Bcl2, and p53 expression [ 119 , 134 ].…”
Section: Pathways Involved In Cancer and Potential Targets To ...mentioning
confidence: 99%